2022
DOI: 10.1186/s40001-022-00693-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of MDA5-positive dermatomyositis complicated by gangrenous cholecystitis with tofacitinib

Abstract: Background Dermatomyositis is a rare idiopathic inflammatory disease with diverse presentations that can have varying degrees of cutaneous and systemic involvement. This phenotypic heterogeneity makes DM a therapeutic challenge. Some therapeutic drugs, such as hormones and immunosuppressants, have poor therapeutic effects. In recent years, tofacitinib has been reported to be effective in the treatment of dermatomyositis. Case presentation We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Notably, ruxolitinib mainly inhibits JAK1 and JAK2 and has moderate activity against tyrosine kinase 2 (TYK2); tofacitinib mainly inhibits JAK1 and JAK3 with less activity against JAK2 and TYK2; and baricitinib has high activity against JAK1 and JAK2, moderate activity against TYK2, and less activity against JAK3 [66, 70,71 && ]. In juvenile [72][73][74][75][76][77][78] and adult [60, patients with refractory dermatomyositis, ruxolitinib, tofacitinib, and baricitinib improved skin lesions [60,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][87][88][89][90]94,97,100], muscle strength [60,[72][73][74][75][76][77][78][79][80]85,94,97], joint symptoms [72,76,77,…”
Section: Update On Dermatomyositismentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, ruxolitinib mainly inhibits JAK1 and JAK2 and has moderate activity against tyrosine kinase 2 (TYK2); tofacitinib mainly inhibits JAK1 and JAK3 with less activity against JAK2 and TYK2; and baricitinib has high activity against JAK1 and JAK2, moderate activity against TYK2, and less activity against JAK3 [66, 70,71 && ]. In juvenile [72][73][74][75][76][77][78] and adult [60, patients with refractory dermatomyositis, ruxolitinib, tofacitinib, and baricitinib improved skin lesions [60,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][87][88][89][90]94,97,100], muscle strength [60,[72][73][74][75][76][77][78][79][80]85,94,97], joint symptoms [72,76,77,…”
Section: Update On Dermatomyositismentioning
confidence: 99%
“…In juvenile [72][73][74][75][76][77][78] and adult [60, patients with refractory dermatomyositis, ruxolitinib, tofacitinib, and baricitinib improved skin lesions [60,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][87][88][89][90]94,97,100], muscle strength [60,[72][73][74][75][76][77][78][79][80]85,94,97], joint symptoms [72,76,77,82,92,94,96], ILD [75]…”
Section: Update On Dermatomyositismentioning
confidence: 99%
See 2 more Smart Citations
“…However, on extensive literature search of clinical images of dermatomyositis, we came across some suggestions of similar involvement in other patients with anti-MDA-5 dermatomyositis. [2][3][4] Whether or not this sign is suggestive or specific for this antibody and its prognostic implication and association with airway/lung involvement remains to be established. In one review, the authors noted 4 of 10 patients who were anti-MDA-5 positive reported tender gums and/or oral erosions, significantly more than the group that was anti-MDA5 negative.…”
mentioning
confidence: 99%